5x+(-8)=-2

Simple and best practice solution for 5x+(-8)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+(-8)=-2 equation:


Simplifying
5x + (-8) = -2
5x + -8 = -2

Reorder the terms:
-8 + 5x = -2

Solving
-8 + 5x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 5x = -2 + 8

Combine like terms: -8 + 8 = 0
0 + 5x = -2 + 8
5x = -2 + 8

Combine like terms: -2 + 8 = 6
5x = 6

Divide each side by '5'.
x = 1.2

Simplifying
x = 1.2

See similar equations:

| 2x^2-8x+3=x^2-3x-3 | | 8x-11(x-2)=45 | | 585=(X*3.5^1.25)/22.5^0.5 | | 2/3-x=5/6 | | (4y^2)-1=0 | | 3x^2-5x+7=x^2+2x+1 | | 5.4(4+2x)-7.6=14 | | 6+x/6=-1.68 | | 7/6x-7=10/3x+10 | | 9=19-1y | | 5+a/6=8 | | 4(x-3)=3x-7[4] | | 8y+5x=0 | | 16x^2-24x-5=0 | | 9y^2-36=0 | | 6+1/5x=2 | | 1/2w=-9 | | 3/-8*2/7*-3 | | 36/0.04 | | 8x^2+77x+45=0 | | Ln(lne)=4lnx | | 4/9*7*-3/-8 | | -9/6*2/-5*-7 | | 4-m/3=9 | | 2.1(1.1y+3.4)=-2.4 | | -3xsquared=21x+36 | | 3*1/2 | | E=100(2) | | 5x-7=x+13 | | 4*-5/-3*-2/9 | | 4-2w=(3w-7) | | 5+n/4=10 |

Equations solver categories